2017
DOI: 10.1111/jog.13511
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers and prenatal management of isolated fetal complete atrioventricular block: A retrospective review at a single institution

Abstract: An anti-Ro level of 32× could be the threshold value for CAVB development. Prenatal anti-inflammatory treatment in patients with CAVB and prophylactic PEX in patients who had an affected child may have the potential to improve pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been confirmed that the earlier subjective symptoms of ICP appear (itching of the skin), then the risk of an early delivery happening increases, which could be a result of the unfavorable effects of bile acids on the fetus being elongated (Murakami et al, ). On the basis of previous research, it has been determined that a statistically significant increased risk of an early delivery happening as well as the occurrence of serious fetal damage occurs when the bile acid levels passes 40 μmol/l in the blood (Glantz, Marschall, Lammert, & Mattsson, ).…”
Section: Discussionmentioning
confidence: 93%
“…It has been confirmed that the earlier subjective symptoms of ICP appear (itching of the skin), then the risk of an early delivery happening increases, which could be a result of the unfavorable effects of bile acids on the fetus being elongated (Murakami et al, ). On the basis of previous research, it has been determined that a statistically significant increased risk of an early delivery happening as well as the occurrence of serious fetal damage occurs when the bile acid levels passes 40 μmol/l in the blood (Glantz, Marschall, Lammert, & Mattsson, ).…”
Section: Discussionmentioning
confidence: 93%